GROWING AN INTERNATIONAL MOVEMENT FOR PLANT CONSERVATION AND PLANT RESOURCE MANAGEMENT: THE DEVELOPMENT OF THE INTERNATIONAL BOTANIC GARDEN COMMUNITY - Jackson, Peter Wyse (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2009)
The last twenty to thirty years can be said to constitute a new renaissance botanical gardens around the world. One of the main causes is the growing concern of the world community associated with the issue of loss of biodiversity. In addition, because a greater need to be institutions that take part actively in the field of conservation of plant resources. Community botanical garden world is experiencing rapid development, not only in terms of the number of new botanical garden that is built up but also of the purpose and function. There are currently no less than 2,500 botanical gardens worldwide. To prepare for a global framework for policies, programs and priorities of the botanical garden world in the field of conservation of biodiversity, in 2000 BGCI has published the International Agenda for Botanic Gardens in Conservation, which contained the botanical gardens global mission.